Praperadilan Terhadap Penetapan Tersangka Tindak Pidana Korupsi Dalam Sistem Peradilan Pidana Indonesia - Wilda Rizki; Santrawan T. Paparang; Kristiawanto Kristiawanto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Indonesia is a state of law (rechstaat) not based on mere power (machstaat), as stated in the preamble, body, and explanation of the 1945 Constitution. The state of the law has a nature where the equipment can only act according to and be bound by the rules which have been determined in advance, by the equipment which is authorized to enforce the regulation. In conducting the search for the truth of a criminal act, there is the principle of